The role of tumor-associated macrophages and PD-1/PD-L1 networking in colorectal cancer - Yerolatsite, Melina; Torounidou, Nanteznta; Amylidi, Anna-Lea; Zarkavelis, George; Hadjigeorgiou, Loizos; Lampri, Evangeli; Bali, Christina; Georvasili, Vaia; Kampletsas, Eleftherios; Mauri, Davide (Contemporary Oncology/Współczesna Onkologia, 2025)
Colorectal cancer (CRC) is the fourth most common cancer worldwide and a leading cause of cancer-related mortality. Despite improvements in cancer prevention, early diagnosis, and therapeutic options, metastatic CRC (mCRC) remains a major challenge, with a significantly lower 5-year survival rate compared to localized CRC. The heterogeneity of CRC, both localized and metastatic, necessitates a thorough molecular characterization to guide treatment strategies. A significant aspect of CRC progression involves the tumor microenvironment, particularly tumor-associated macrophages (TAMs), which are abundant and exhibit high plasticity. Tumor-associated macrophages, especially those polarized into the M2 phenotype, support various aspects of tumor progression, including angiogenesis, metastasis, and immune evasion. The PD-1/PD-L1 immune checkpoint axis, overexpressed in M2 TAMs, contributes to immune suppression, facilitating tumor growth. While some studies suggest that TAMs may have a positive role in CRC prognosis, others associate TAM infiltration with poor outcomes, particularly in metastatic disease. The relationship between TAMs and the PD-1/PD-L1 axis in CRC is still not fully understood, though emerging data highlight their potential to shape the immune resistance environment. Further research is needed to clarify the role of TAMs and the PD-1/PD-L1 network in CRC progression and to develop more effective immunotherapies targeting these pathways. This review systematically explores the current literature on TAMs and their interaction with the PD-1/PD-L1 axis in CRC, emphasizing the need for continued investigation to improve patient outcomes.